Expression and activation of TGF-β isoforms in acute allergen-induced remodelling in asthma. Issue 4 (24th January 2007) - Torrego, Alfons; Hew, Mark; Oates, Tim; Sukkar, Maria; Fan Chung, Kian
Abstract : Background: Airway wall remodelling and inflammation are features of chronic asthma. Transforming growth factor β (TGF-β) has been implicated in these processes. Aim: To determine the effect of allergen challenge on airway inflammation and remodelling and whether TGF-β isoforms and the Smad signalling pathways are involved. Methods: Thirteen patients with atopic asthma underwent inhalational challenge with 0.9% saline, followed by allergen 3–4 weeks later. After both challenges, fibreoptic bronchoscopy was undertaken to obtain bronchial biopsies and tissue samples were processed for immunohistochemistry and examined by microscopy. Results: Forced expiratory volume in 1 s (FEV1 ) fell after allergen challenge (mean (SE) −28.1 (0.9)% at 30 min with a late response at 7 hours (−23.0 (1.2)%). Allergen challenge caused an increase in neutrophils and eosinophils in the bronchial mucosa compared with saline. Sub-basement membrane (SBM) thickness did not change after allergen, but tenascin deposition in SBM was increased. Intranuclear (activated) Smad 2/3 and Smad 4 detected by immunohistochemistry were increased after allergen challenge in epithelial and subepithelial cells of bronchial biopsies. No inhibitory Smad (Smad 7) protein was detected. TGF-β isoforms 1, 2 and 3 were expressed predominantly in bronchial epithelium after saline and allergen challenges, but only TGF-β2 expression was increased after allergen. Double immunostaining showed an increase in TGF-β2 positive eosinophils and neutrophils but not in TGF-β1 positive eosinophils and neutrophils after allergen challenge. Conclusions: TGF-β2 may contribute to the remodelling changes in allergic asthma following single allergen exposure.